Substandard and falsified medicines in the UK: a retrospective review of drug alerts (2001-2011) - Almuzaini, Tariq; Sammons, Helen; Choonara, Imti (BMJ Publishing Group, 2013)
Objective: To determine the extent of substandard and falsified medicines in the UK. Design: A retrospective review of drug alerts and company-led recalls. Setting: The Medicines and Healthcare Products Regulatory Agency (MHRA) website search for drug alerts issued between 2001 and 2011. Eligibility criteria: Drug alerts related to quality defect in medicinal products. Main outcome measure: Relevant data about defective medicines reported in drug alerts and company-led recalls, including description of the defect, type of formulation, year of the alert and category of the alert. Results: There were 280 substandard medicines of which 222 were recalled. The two most frequent problems were contamination (74 incidents) and issues related to packaging (98 incidents). Formulations for parenteral administration (117 incidents) were the formulation most frequently affected. There were 11 falsified medicines, as defined by the MHRA, reported over the 11-year period. The number of defective medicines reported by the MHRA increased 10-fold from 5 in 2001 to 50 in 2011. Conclusions: Substandard medicines are a significant problem in the UK. It is uncertain whether the increasing number of reports relates to improved detection or an increase in the number of substandard medicines